Pengaruh Penyaluran Kredit dan Kredit Bermasalah terhadap Rasio Kecukupan Modal: The Influence of Credit Disbursement and Non-Performing Loans on the Capital Adequacy Ratio - Nur, Meilani; Rahmawati, Dayyinah Ayunda (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to analyze the influence of credit distribution and non-performing loans (NPL) on the capital adequacy ratio (CAR) in the Indonesian banking sector. The research population includes all banks within the Indonesian banking industry, while the sample consists of conventional commercial banks listed under the Financial Services Authority (OJK) for the period 2014-2022. The study applies classical assumption tests such as normality and autocorrelation tests and examines the relationship between variables using SPSS 24. The data analysis is conducted through multiple linear regression. The results reveal that both credit disbursement and non-performing loans (NPL) have a significant and positive impact on banks' CAR. This outcome indicates that while banks continue to extend credit, they are also able to maintain adequate capital levels, suggesting effective risk management and regulatory compliance in handling credit risks.